Teenagers knowledge about contraception and pregnancy aged between thirteen and nineteen years - Thekiso, Mothwana Mmule (My University, 2014)
Teenage pregnancy is a major problem in Botswana. The purpose of the study was to find out to what extent teenagers are knowledgeable about the use of contraceptives and pregnancy. The sample comprised subjects aged 13-19 years from five secondary schools in the Central District, Botswana. One hundred-and-thirty-two students completed self-administered questionnaires. The type of .esearch methodology used was a descriptive survey. Information obtained included: demographic data, socio-economic status, religious background, marital status of parents, knowledge on contraception and pregnancy. The results showed that 61.4% of participants were females, 96.3% of participants were Batswana and 59.2% were aged 17-19 years. The majority of participants (61.4%) were from Form I and Form II. The results also showed that 69% of participants were from a family of five and more, 52.3% indicated that they have been staying in their current residential area for 7 years and more. The results also show that 59% indicated that the breadwinners in their families were their fathers. 21.5% of the respondents indicated that they belonged to the Zion Christian Church. From 64% of participants who indicated that their parents were married, 55.3% indicated that their parents were still staying together. The majority of participants (81.8%) in this study indicated that they had knowledge about contraception and 31.8% of participants listed one method of contraceptive they knew. The results showed that the majority of participants (85.6%) had knowledge on the use of contraceptives but 53% of sexually active teenagers indicated that they did not use contraceptives. The results showed that 81.7% indicated that they knew how pregnancy occurs.